Ultrastructure of the eggshell of the leatherback turtle, (Dermochelys coriacea) - Chan, E. H. (1989)
The ultrastructure of eggshell of the leatherback turtle, Dermochelys coriacea, was investigated using scanning electron microscopy. The basic structure was found to conform to that described for other chelonians. The eggshell consisted of an inner organic membranes and an outer inorganic or mineral layer of calcium carbonate deposited normally as aragonite crystals and occasionally as calcite which is considered an aberrant crystal form. The mineral layer is covered in part by an amorphous layer of organic material. In some samples, theouter organic matrix was accompanied by a layer of sperical units of variable size which frequently coalesced to form a cement-like structure. This additional layer has not been described for the leatherback or other chelonians,but is encountered in eggs of avians which have undergone stress. The possible cause and effects of this abnormal structure is discussed.